METHODS FOR IMPROVING WRITING TECHNIQUES IN INCLUSIVE PRIMARY EDUCATION - Alimardanova Sitora Ikrom kizi (International Journal of Literature and Language Studies, 2026)
This article examines effective methods for improving writing techniques among primary school pupils in inclusive education. Particular attention is paid to the writing difficulties experienced by children with special educational needs, including impaired fine motor coordination, visual–motor integration problems, weak spatial orientation, difficulties in controlling writing pressure, and reduced learning motivation. The article analyses pedagogical, corrective, technological, and individualized approaches to developing handwriting skills in inclusive classrooms. Methods such as fine motor exercises, multisensory instruction, differentiated tasks, graphic exercises, adaptive writing tools, assistive technologies, step-by-step modelling, and formative assessment are described. The study emphasizes that the improvement of writing techniques requires cooperation among primary school teachers, special education specialists, psychologists, speech therapists, occupational therapists, parents, and pupils.